Hubungan Luar Negeri Provinsi Maluku dengan Selandia Baru dalam Mengembangkan Energi Terbarukan - Abdullah Randika Anwar; Windy Dermawan; RMT Nurhasan Affandy; Gilang Nur Alam (Universitas Diponegoro, 2021)
Maluku Province is one of the regions that has the potential for renewable energy resources which are quite abundant, but they have not been utilized properly due to various obstacles and challenges in the region. In order to overcome the existing problems, Maluku Province has established foreign relations with the Government of New Zealand through the New Zealand Booking program - Maluku Access to Renewable Energy Support (NZMATES) starting from April 2018 to June 2023. This research aims to describe how the efforts taken by the Maluku Provincial Government and the New Zealand Government in developing renewable energy in the Maluku region. By using qualitative methods with data techniques through literature studies and internet-based document searches, this article argues that through the establishment of foreign relations between Maluku Province and New Zealand through the formation of NZMATES it can help and facilitate the process of developing renewable energy in the Maluku region. NZMATES can create a more competent work environment by engaging with several agencies with regional interests to participate in developing renewable energy in Maluku Province.